Evaluation of retinal pigment epithelium–Bruch's membrane complex thickness in dry age-related macular degeneration using optical coherence tomography. Issue 10 (10th July 2013) - Karampelas, Michael; Sim, Dawn A; Keane, Pearse A; Papastefanou, Vasilios P; Sadda, Srinivas R; Tufail, Adnan; Dowler, Jonathan
Abstract : Aim: To compare retinal pigment epithelium–Bruch's membrane (RPE–BM) complex thickness in patients with early and intermediate dry age-related macular degeneration (AMD) and age-matched controls using spectral domain optical coherence tomography (SD-OCT). Methods: In this retrospective, cross-sectional study, 25 patients with dry AMD and 25 controls were recruited. SD-OCT scans were manually segmented by two independent investigators. Thickness values were calculated for the nine Early Treatment Diabetic Retinopathy Study (ETDRS) subfields. Results: RPE–BM thickness was significantly thicker in the dry AMD group (32.3, 30.6 and 28.4 μm for central, inner and outer subfields, respectively) compared with the normal eyes (22.7, 21.8 and 21.6 μm, respectively). RPE–BM thickness was positively correlated with age in the normal group but not in the AMD group. RPE–BM thickness in the dry AMD group was negatively correlated with visual acuity in the central and inner subfields but not in the outer. We observed good intraobserver and inter-observer reliability for both groups in all ETDRS subfields. Conclusions: This study reports novel data concerning RPE–BM segmentation in dry AMD and performs a direct comparison with age-matched normal controls. Our findings confirm the electron and light microscopy derived data and also establish the value of OCT in the quantification of the RPE–BM complex.